2007
DOI: 10.1139/h07-059
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of a hypocaloric high-protein diet, with and without exercise, on weight loss, fitness, and markers of the Metabolic Syndrome in overweight and obese women

Abstract: The purpose of this study was to examine the effects of 3:1 and 1:1 carbohydrate to protein ratios, hypocaloric diets with and without exercise, and risk factors associated with the Metabolic Syndrome in overweight and obese Canadian women. Groups were designated as control diet (CON), control diet with exercise (CONEx), high-protein (HP), or high-protein with exercise (HPEx). Free-living women from the Guelph community were studied in a university health and fitness facility. The participants were 44 of 60 ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
97
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(108 citation statements)
references
References 17 publications
7
97
4
Order By: Relevance
“…Diets rich in protein and low glycaemic index carbohydrates also improve satiety and avoid or reduce excess weight gain 39,48,119 . Animal and human studies also show that fat intake is potentially linked to overeating and a positive energy balance 44,120 , although high fat diets do not necessarily cause weight gain 52,53 , and lowcarbohydrate diets (high-protein or high fat) have shown to be as effective as control or low-fat diets in weight loss treatments 35,37,40,54,68 Furthermore, the advances in bioinformatics and 'omics' technologies may herald a new era in personalized medicine, 121 although applications of epigenetic and genome-wide profiling are some way from clinical implementation or global consensus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diets rich in protein and low glycaemic index carbohydrates also improve satiety and avoid or reduce excess weight gain 39,48,119 . Animal and human studies also show that fat intake is potentially linked to overeating and a positive energy balance 44,120 , although high fat diets do not necessarily cause weight gain 52,53 , and lowcarbohydrate diets (high-protein or high fat) have shown to be as effective as control or low-fat diets in weight loss treatments 35,37,40,54,68 Furthermore, the advances in bioinformatics and 'omics' technologies may herald a new era in personalized medicine, 121 although applications of epigenetic and genome-wide profiling are some way from clinical implementation or global consensus.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, 68 44 overweight or obese women were assigned to one of two energy-restricted dietary programs (carbohydrate:protein ratios of either 3:1 or 1:1), with or without regular exercise. 68 After 12 weeks, women in the high-protein diet plus exercise group had lost an average of 7 kg, whereas the control (standard-protein diet, no exercise) group achieved an average weight loss of 2.1 kg. The high-protein, no-exercise group also achieved an average weight loss of 4.6 kg.…”
Section: Exercise-related Interventionsmentioning
confidence: 99%
“…Two trials were subsequently identified in the update search (Toscani et al, 2011;Gogebakan et al, 2011) Fasting total cholesterol 5.50. Twenty three randomised controlled trials that presented evidence on diets differing in the proportion of carbohydrate to protein and fat on fasting total cholesterol were included in the meta-analysis (Clevidence et al, 1992;Golay et al, 1996;Brehm et al, 2003;Johnston et al, 2004;Meckling et al, 2004;Brehm et al, 2005;Dansinger et al, 2005;Ebbeling et al, 2005;Layman et al, 2005;Krauss et al, 2006;McMillan-Price et al, 2006;Noakes et al, 2006;Keogh et al, 2007;Mahon et al, 2007;Meckling & Sherfey, 2007;Maki et al, 2007b;Keogh et al, 2008;Lasker et al, 2008;Phillips et al, 2008;Stoernell et al, 2008;Sacks et al, 2009;de Luis et al, 2009b). Five trials were subsequently identified in the update search (Al-Sarraj et al, 2010;Krebs et al, 2010;Klemsdal et al, 2010;Lim et al, 2010;Wycherley et al, 2010) (Cardiometabolic review, the hyperlipidaemias and blood lipids chapter p 70-71; Update search table 72).…”
Section: Fasting Triacylglycerolmentioning
confidence: 99%
“…Seven randomised controlled trials were identified that presented evidence on diets differing in the proportion of carbohydrate to protein and fat on systolic and diastolic blood pressure, all of which were included in the meta-analysis (Brehm et al, 2003;Meckling et al, 2004;Brehm et al, 2005;Keogh et al, 2007;Meckling & Sherfey, 2007;Keogh et al, 2008;de Luis et al, 2009b). Three trials were subsequently identified in the update search (Klemsdal et al, 2010;Lim et al, 2010;Wood et al, 2012) (Cardiometabolic review, incident hypertension and blood pressure chapter p 52, 56; Update search table 49).…”
mentioning
confidence: 99%
“…Finally, a series of studies investigating the carbohydrate to protein ratio of diets as a determinant of weight loss showed ratios (1.0-1.4) corresponding to 1.0-1.6 g/kg protein produced more weight loss than ratios (3.0-3.5) corresponding to 0.7-0.8 g/ kg protein with 20, 21 or without 39 exercise in short-term interventions. However, many studies failed to find significant differences in weight loss between low-and high-protein diets.…”
mentioning
confidence: 99%